REVIEW ARTIKEL: TINJAUAN AKTIVITAS FARMAKOLOGI KULIT BAWANG MERAH (Allium cepa aggregatum group) - nurihardiyanti nurihardiyanti; Tania Rizki Amalia; Andriyani Rahmah Fahriati (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
Herbal medicine is widely used and trusted by the community . and trusted by the public to treat various diseases.One of the plants that is often used is onion. Shallots are widely used or often consumed by the public as a kitchen spice, which is widely known by the public. In addition, red onion is often used by the community for alternative medicine because this plant is widely available in the community and is easy to obtain, only the skin is discarded because it is considered useless and is only used as waste. Shallot skin has many pharmacological activities, especially if it is in the form of an extract. The pharmacological activities of bay leaves include antibacterial, anti-inflammatory, antidiabetic, antioxidant, hepatoprotector and hyperuricemia. The content of onion skin is allicin, aliin, phenolic acid, flavonoids, quercetin, saponins, flavonoids, polyphenols, saponins, terpenoids and alkaloids, onion skin also contains various chemical compounds, namely proteins, minerals, sulfur anthocyanins, kaemferol, carbohydrates, and fiber. . In this review, primary data searches are conducted online, in the form of national and international journals, books and ebooks. The results obtained from several journals and other sources can be known various kinds of pharmacological activities of onion peel extract.